2020
DOI: 10.1101/2020.02.12.945675
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pantoea ananatisdefeatsAlliumchemical defenses with a plasmid-borne virulence gene cluster

Abstract: Onion (Allium. cepa L), garlic (A. sativum L.), and other members of the Allium genus produce volatile antimicrobial thiosulfinates upon cellular damage. Allicin has been known since the 1950s as the primary antimicrobial thiosulfinate compound and odorant produced by garlic. However, the roles of endogenous thiosulfinate production in host-bacterial pathogen interactions have not been described. The bacterial onion pathogen Pantoea ananatis, which lacks both the virulence Type III and Type II Secretion System… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(36 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…It is intriguing to speculate that the syntenic region might help overcome the oxidative burst associated with plant defense, as well as protecting against more specifically redox-active sulfur-containing plant defense substances such as allicin, and it would be interesting to see if loss of syntenic genes other than dsbA in Pst DC3000 also leads to a reduction of virulence. Moreover, a recent study reported plasmid-born onion virulence regions in Pantoea ananatis strains that are pathogenic on onion (Stice et al, 2018, 2020. The OVRA region contained a subset of genes that we describe in our present study as allicin resistance genes.…”
Section: Discussionmentioning
confidence: 50%
“…It is intriguing to speculate that the syntenic region might help overcome the oxidative burst associated with plant defense, as well as protecting against more specifically redox-active sulfur-containing plant defense substances such as allicin, and it would be interesting to see if loss of syntenic genes other than dsbA in Pst DC3000 also leads to a reduction of virulence. Moreover, a recent study reported plasmid-born onion virulence regions in Pantoea ananatis strains that are pathogenic on onion (Stice et al, 2018, 2020. The OVRA region contained a subset of genes that we describe in our present study as allicin resistance genes.…”
Section: Discussionmentioning
confidence: 50%
“…In this scenario, the alt cluster helps P. ananatis survive and colonize onion plants. P. ananatis uses 11 alt cluster genes associated with sulfur metabolism to impart tolerance to the thiosul nate 'allicin' that is produced by damaged onion cells [26]. The presence of the alt cluster in 80% (n = 41) of the onion pathogenic strains, and its absence in 67% (n = 20) of the non-pathogenic strains, suggests some potential involvement in bacterial virulence.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Stice et al [25] showed that a megaplasmid-borne onion virulence region (OVR) in P. ananatis is correlated with onion virulence. In a recent study, Stice et al [26] showed that the OVRA cluster contains 11 genes that are critical for colonizing necrotized bulb tissue. This gene cluster was described as the 'alt' cluster that imparts bacterial tolerance to the thiosul nate 'allicin' in onion bulbs.…”
Section: Introductionmentioning
confidence: 99%
“…ananatis uses 11 alt cluster genes associated with sulfur metabolism to impart tolerance to the thiosulfinate 'allicin that is produced by damaged onion cells [26]. In this study, we demonstrated the use of a pan-GWAS approach to predict genes associated with onion-pathogenicity in P. ananatis.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, Stice et al [25] showed that a megaplasmid-borne onion virulence region (OVR) in P. ananatis is correlated with onion virulence. In a recent study, Stice et al [26] showed that the OVRA cluster contains 11 genes that are critical for colonizing necrotized bulb tissue. This gene cluster was described as the 'alt' cluster that imparts bacterial tolerance to the thiosulfinate 'allicin' in onion bulbs.…”
Section: Introductionmentioning
confidence: 99%